ANALISIS PELAKSANAAN PEMASARAN DALAM PENJUALAN PRODUK AIR MINERAL (STUDI KASUS PT. TRI TIRTA MEGAH PEKANBARU) - Rizka Nasyella; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was conducted at PT. Tri Tirta Magnificent Pekanbaru is located at No. 8 JalanLaksamana Datuk Gobah Pekanbaru. Formulation of the problem in this study is How theMarketing Execution Analysis in Mineral Water Product Sales (Case Study PT. MagnificentTri Tirta Pekanbaru).?. The purpose of this research is to know the Marketing ExecutionAnalysis in Mineral Water Product Sales (Case Study PT. Magnificent Tri Tirta Pekanbaru).Techniques of data collection using questionnaires.Based on the results of research conducted found that PT Tirta Tri Megah Pekanbaruimplement four (4) factors that affect the sale of mineral water products at Tri Tirta PT MegahPekanbaru namely improving the quality of services, the determination of the level of bonuses,promotions and low prices for customers, improving service services. Of the four factors areapplied, the business improvement services are the most successful businesses. This is due tothe location oprsional Megah PT Tri Tirta Pekanbaru close to the crowd / market. The surveyresults revealed that the low consumer tastes change employee culture is an obstacle faced byPT Tri Tirta Megah Pekanbaru. The existence of other products such as bottled waterpackaging that provides a variety of advantages, resulting in changes in consumer appetite formineral water products.Key Word: Quality, Distribution, Service, Promotion